(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to identify the role of artificial intelligence technologies in improving the consideration of individual differences among students in the basic education stage in Libya. This is achieved through examining teachers’ perspectives on the reality of individual differences and the possibility of benefiting from artificial intelligence technologies in the educational process within schools. The study adopted the descriptive-analytical approach and used a questionnaire as the main tool for data collection from a sample of 46 male and female teachers from the basic education stage in several Libyan cities. The results revealed clear individual differences among students in terms of comprehension, understanding, response speed, and academic achievement. The findings also indicated that class overcrowding, weak parental follow-up, and limited class time are among the most significant factors influencing these differences. In addition, the results showed a positive attitude toward the use of artificial intelligence technologies in education, as participants confirmed the possibility of benefiting from these technologies in providing more flexible learning that meets the diverse needs of students. On the other hand, the study revealed several challenges facing the implementation of artificial intelligence in Libyan schools, including weak technological infrastructure, a lack of devices, and the need to train teachers on the effective use of artificial intelligence tools. The study findings also indicate that employing artificial intelligence technologies in basic education can contribute to improving the consideration of individual differences among students, provided that appropriate infrastructure is available and teachers are adequately trained to use these technologies effectively.